Targeting autophagy in astrocytes: a potential for neurodegenerative disease intervention - Potokar, Maja; Jorgačevski, Jernej (Frontiers in Cellular Neuroscience, 2025)
Autophagy contributes to cellular homeostasis by regulating the degradation and recycling of damaged organelles and misfolded proteins. In the central nervous system (CNS), impaired autophagy contributes to inflammation, disrupts cellular metabolism, and leads to the accumulation of toxic protein aggregates that accelerate the progression of neurodegenerative diseases. In addition to its role in protein and organelle turnover, autophagy facilitates the elimination of pathogenic bacteria and viruses, whose infections can also lead to neurological diseases and neuroinflammatory processes. Astrocytes, the most abundant glial cells in the CNS, play a crucial role in maintaining neuronal homeostasis by regulating neurotransmitter balance, ion exchange, and metabolic support. During neurodegeneration, they become reactive, actively participating in neuroinflammatory responses by releasing proinflammatory cytokines, activating microglia, and removing toxic aggregates. Cytokine-mediated responses and metabolic changes in astrocytes influence neuronal viability and neurotransmission. Autophagy in astrocytes plays an important role in tuning the astrocyte-dependent activity of neurons under physiological conditions and in pathological activation of astrocytes by disease, injury or pathogenic stimuli. In this review, we highlight the contribution of astrocytes to neurodegeneration from the perspective of changes in their cytoskeleton, the autophagy process in which the cytoskeleton plays a crucial role, and the metabolic support of neurons. The modulation of autophagy at different stages has the potential to serve as an additional therapeutic target in CNS diseases.